The testing of the hypothesis of homogeneity of the variance for linearly arranged random sequences - Bondarenko, V. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. Н. Бондаренко. Проверка гипотезы об однородности дисперсии для линейно упорядоченных случайных последовательностейV. Bondarenka. Hipotezės apie tiesiškai sutvarkytų atsitiktinių dydžių sekų dispersijos homogeniškumą patikrinimas